Cisplatin enhances NK cells immunotherapy efficacy to suppress HCC progression via altering the androgen receptor (AR)-ULBP2 signals. Issue 1 (1st April 2016) - Shi, Liang; Lin, Hui; Li, Gonghui; Sun, Yin; Shen, Jiliang; Xu, Junjie; Lin, Changyi; Yeh, Shuyuan; Cai, Xiujun; Chang, Chawnshang
Highlights: Help to explain gender disparity in HCC from a novel aspect, innate immune and AR. Raising a potential therapy by targeting AR in HCC to elevate ULBP2 with cisplatin. Providing new ideas about therapy combination like immunotherapy with chemotherapy. Help to better select HCC patients for cisplatin treatment based on AR expression. Abstract: The aim of this study is to investigate the influence of cisplatin on the efficacy of natural killer (NK) cells immunotherapy to suppress HCC progression, and provide valuable information on better application of cisplatin in clinical settings. By using in vitro cell cytotoxicity test and in vivo liver orthotopic xenograft mice model, we identified the role of cisplatin in modulating NK cells cytotoxicity. Luciferase report assay and chromatin immunoprecipitation assay were applied for mechanism dissection. Immunohistochemistry is performed for sample staining. We found cisplatin could enhance the efficacy of NK cells immunotherapy to better suppress HCC progression via altering the androgen receptor (AR)-UL16-binding protein 2 (ULBP2) signals both in vitro and in vivo. Mechanism dissection revealed that cisplatin could suppress AR expression via two distinct ways: increasing miR-34a-5p to suppress AR expression and altering the ubiquitination to accelerate the AR protein degradation. The suppressed AR might then function through up-regulating ULBP2, a natural-killer group 2 member D ligand, to enhance the cytotoxicity of NK cells. Together, these results indicated an unrecognized favoring effect of cisplatin in HCC treatment. By suppressing AR in HCC, cisplatin could up-regulate cytotoxicity of NK cells to better target HCC. This finding may provide a potential new approach to control HCC by combining traditional chemotherapy with immunotherapy.